Management of Motorcycle Workshops of SMEs Scale Based on Information System - Arief, Dodi Sofyan; Susilawati, Anita; Simaskot, Johar; Badri, Muftil; Dalil, M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
The good workshop management must also be supported by a properly administration, in order to record all the resources that become workshop assets. Moreover, the motorcycle workshop also conducts spare parts sales to complete the replacement needs of broken vehicle spare parts. This study aims to analyze and design a workshop information system for Small and Medium Enterprises (SMEs) engaged in the field of repairing of motorcycle. Generally, the SMEs scale of motorcycle workshops in this research still uses a simple management system and manually in presenting the data required by the workshop. This it make difficult and inconvenient for the owner of a SMEs scale of motorcycle workshop. Sequence, it is necessary to optimalize the management system from the simpler manual system to be computerized. Stages of the method in this study: (1) survey of general workshop management SMEs scale, (2) do analysis of data obtained during the survey and provides input for workshop management based on 5S method, (3) to design and create information systems and databases using PHP (Hypertext Preprocessor) as the programming language and MySQL as the database. The approach of the 5S (Sort, Straighten, Shine, Standardize, Sustain) and creating an information system can manage equipments and properly administration in SMEs scale of motorcycle workshops. Therefore, they can help to optimize streamline the services and administration activity of SMEs scale of motorcycle workshops.